THE RELATIONSHIP BETWEEN ORGANIZATIONAL COMMITMENT AND PRODUCTIVITY OF EMPLOYEES OF PT X - Gori, Yarni Indah Chariani; Simarmata, Nenny Ika Putri (Dharmas Education Journal (DE_Journal), 2023)
This study aims to examine the relationship between organizational commitment and productivity in employees at PT X. Organizational commitment is one of the important factors that can affect business productivity. Highly committed employees tend to be more loyal, motivated and contribute optimally to achieve organizational goals. In this study, the quantitative method used by the survey method, where the questionnaire was distributed to 110 answers selected by the researcher. The data obtained were then analyzed using a statistical correlation test to measure the level of relationship between the two variables. The results of the study showed a value of 0.816, indicating a positive and significant relationship between organizational commitment and employee productivity. In other words, the higher the commitment to the organization, the more productivity can be achieved. Based on these results, it is recommended that companies improve strategies in creating employee commitment, such as through career development, reward systems and creating a supportive work environment